KARAKTER PARA NABI DAN IMPLEMENTASINYA DALAM PEMBELAJARAN PAI DI SEKOLAH - Santy Dewi, - (2023)
Karakter merupakan watak atau tingkah laku yang melekat pada diri seseorang yang diekspresikan dalam kehidupan sehari-hari. Beberapa kasus kekerasan anak yang disebutkan oleh kemen PPPA, terlihat perilaku sebagian remaja Indonesia yang sama sekali tidak mencerminkan sebagai remaja yang berakhlak baik. Karakter para Nabi tentu penting diimplementasikan dalam pembelajaran PAI agar terwujud generasi yang lebih baik. Penelitian ini bertujuan untuk menganalisis Karakter Para Nabi dan Implementasinya dalam Pembelajaran PAI di Sekolah, agar mengetahui bagaimana Karakter-karakter para Nabi sehingga bisa diimplementasikan dalam pembelajaran PAI. Adapun poin-poin yang akan dianalisis di antaranya yaitu: karakter Nabi Nuh a.s, karakter Nabi Ibrahim a.s, karakter Nabi Yakub a.s. dan implementasinya dalam pembelajaran PAI di sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Sumber data penelitian ini adalah buku tafsir Ibnu Katsir, Tafsir Al-Misbah, 25 Nabi dan Rosul. Pengumpulan datanya yaitu dengan studi dokumen. Analisis datanya yaitu analisis isi dengan langkah-langkah reduksi data, display data, dan verifikasi data. Hasil dari penelitian menunjukkan bahwa karakter Nabi Nuh a.s, Nabi Ibrahim a.s, dan Nabi Yakub a.s. yang penyabar, penyayang, kerja keras, taat kepada Allah Swt., menjunjung tinggi ketauhidan, jujur dan ikhlas lalu tidak sombong bisa di implementasikan melalui perencanaan pembelajaran, proses pembelajaran PAI dalam penugasan dan juga pemberian materi oleh guru. Character is a character or behavior that is inherent in a person which is expressed in everyday life. In several cases of child abuse mentioned by the PPPA ministry, it can be seen that the behavior of some Indonesian youths does not reflect that they are teenagers with good morals. The character of the Prophets is of course important to be implemented in PAI learning in order to create a better generation. This study aims to analyze the Characteristics of the Prophets and Their Implementation in Islamic Religious Education Learning in Schools, in order to find out how the Prophets' Characters can be implemented in Islamic Religious Education learning. The points that will be analyzed include: the character of Prophet Noah as, the character of Prophet Ibrahim as, the character of Prophet Jacob as and their implementation in PAI learning in schools. This study uses a qualitative approach with the method of library research (library research). The source of the research data is the commentary book of Ibn Kathir, Tafsir Al-Misbah, 25 Prophets and Messengers. The data collection is by document study. Data analysis is content analysis with data reduction, data display, and data verification steps. The results of the study show that the characters of Prophet Nuh as, Prophet Ibrahim as, and Prophet Jacob as who are patient, compassionate, hard working, obedient to Allah SWT, uphold monotheism, honest and sincere and not arrogant can be implemented through learning planning, process PAI learning in assignments and also the provision of material by the teacher. Interpretation of Al-Misbah, 25 Prophets and Messengers. The data collection is by document study. Data analysis is content analysis with data reduction, data display, and data verification steps. The results of the study show that the characters of Prophet Nuh as, Prophet Ibrahim as, and Prophet Jacob as who are patient, compassionate, hard working, obedient to Allah SWT, uphold monotheism, honest and sincere and not arrogant can be implemented through learning planning, process PAI learning in assignments and also the provision of material by the teacher. Interpretation of Al-Misbah, 25 Prophets and Messengers. The data collection is by document study. Data analysis is content analysis with data reduction, data display, and data verification steps. The results of the study show that the characters of Prophet Nuh as, Prophet Ibrahim as, and Prophet Jacob as who are patient, compassionate, hard working, obedient to Allah SWT, uphold monotheism, honest and sincere and not arrogant can be implemented through learning planning, process PAI learning in assignments and also the provision of material by the teacher.